A deluxe cosmid vector for transformation of filamentous fungi - Janet L. Taylor; Ira E. Borgmann (Fungal Genetics Reports, 1996)
The cosmid shuttle vector AN26 for the transformation of some filamentous fungi to hygromycin B resistance was constructed from the plasmid vector AN7-1. The features of the cosmid are: (1) a BamHI cloning site, (2) NotI and SfiI restriction sites surrounding the BamHI site for easy removal of the cloned DNA insert, (3) T3 and SP6 RNA polymerase promoters outside the NotI and SfiI sites for generation of end specific probes, and (4) dual cos sites separated by a unique ClaI site to facilitate cloning of non-size-selected DNA.